(untitled) (International Journal of Food and Nutritional Sciences, 2025)
Beta glucan, a naturally occurring non starch polysaccharide composed of D glucose units linked by β glycosidic bonds, is widely found in cereals, fungi, algae, yeast, and certain bacteria. Its unique molecular structure contributes to a range of health promoting effects, including immunomodulation through Dectin 1 receptor binding, cholesterol lowering via increased bile acid excretion, and regulation of postprandial glycemia due to increased intestinal viscosity. Clinical studies have reported up to a 10 percent reduction in LDL cholesterol and modulated glycemic response with regular intake. This review summarizes beta glucan’s bioactivities, including antioxidant, anticancer, antimicrobial, antiviral, and prebiotic properties. Furthermore, its functional characteristics such as water binding capacity, emulsification, and gelling make it a versatile agent in food product development. With increasing interest in functional foods and nutraceuticals, beta glucan emerges as a valuable ingredient for both health enhancement and industrial applications.